Limiting rival's efficiency via conditional discounts - Katja Greer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper studies the impact of a dominant firm's conditional discounts on competitors' learning-by-doing. In a vertical context where a dominant upstream supplier and a competitive fringe sell their products to a single downstream firm, we analyze whether the dominant supplier prefers to off er a discount scheme, as in particular a quantity or market-share discount. In a dynamic setting with complete information and learning-by-doing, short-term market-share discounts and long-run contracts are more pro fitable to the dominant supplier than simple two-part tariff s or quantity discounts. We show that two-part tariff s as well as quantity discounts lead to more learning than market-share discounts, or long-term contracts. Thus, the dominant fi rm's contract choice restricts the competitive fringe's e fficiency gain. Similar results occur for network eff ects.
Keywords: L42; L13; D43; 330